2005
DOI: 10.1074/jbc.m510711200
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Substrate Specificity of the Pim-1 Kinase

Abstract: The Pim kinases are a family of three vertebrate protein serine/ threonine kinases (Pim-1, -2, and -3) belonging to the CAMK (calmodulin-dependent protein kinase-related) group. Pim kinases are emerging as important mediators of cytokine signaling pathways in hematopoietic cells, and they contribute to the progression of certain leukemias and solid tumors. A number of cytoplasmic and nuclear proteins are phosphorylated by Pim kinases and may act as their effectors in normal physiology and in disease. Recent cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
205
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(211 citation statements)
references
References 63 publications
2
205
3
1
Order By: Relevance
“…Alteration of the activities of these molecules can result in cell cycle progression, particularly during the G2/M phase. Pim-3 and Pim-1, but not Pim-2, bind to a consensus peptide substrate (AKRRRHPSGPPTA) with a strikingly high affinity, having K d value in the range of 40-60 nM (Bullock et al, 2005). Thus, it is likely that Pim-3 can phosphorylate these cell cycle regulators similarly as Pim-1.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of the activities of these molecules can result in cell cycle progression, particularly during the G2/M phase. Pim-3 and Pim-1, but not Pim-2, bind to a consensus peptide substrate (AKRRRHPSGPPTA) with a strikingly high affinity, having K d value in the range of 40-60 nM (Bullock et al, 2005). Thus, it is likely that Pim-3 can phosphorylate these cell cycle regulators similarly as Pim-1.…”
Section: Discussionmentioning
confidence: 99%
“…To gain further insight into the mechanism of autophosphorylation, we overlaid the SnRK2.6 catalytic cleft with the structure of Pim-1, which, like the SnRK2s, is a member of the calmodulin-dependent protein kinase-related (CAMK) kinase family. The Pim-1 structure is in active conformation with a bound substrate peptide and the ATP analog AMP-PNP (42). As shown in Fig.…”
Section: Snrk26 Activation Loop Phosphate-acceptor Residues Are In Cmentioning
confidence: 99%
“…22,88,115,116 These structural studies revealed a classic bilobal protein kinase domain architecture and apart from the unique beta hairpin insert located N-terminal to helix αC, all conserved secondary structure elements of typical protein kinases were present ( Figure 4). In protein kinases, the binding site for ATP is located in a deep cavity formed by the two kinase lobes and the connecting hinge region.…”
Section: Pim Kinases As Targets For Cancer Therapy Insights From the mentioning
confidence: 99%
“…7,19 Examination of the substrate sequence specificity of PIM1 revealed strong preference for peptides containing (K/R)3-X-S/T-X (X=neither basic nor large hydrophobic residue) 20 and positional peptide library screens identified a consensus sequence (ARKRRRHPS-GPPTA) that bound with low nM affinity to PIM kinases. 21,22 Mass-spectrometric analysis of Xenopus laevis PIM1 identified potential autophosphorylation sites including serine 190 and threonine 205 both conserved between species. 23 We have recently observed phosphorylation of PIM1 after heterologous expression in E.coli located on residue Ser261.…”
mentioning
confidence: 99%